"Economic development" and gender equality: Explaining variations in the gender poverty gap after socialism - Éva Fodor; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, 2015)
Using the 2008 cross-sectional wave of the survey Statistics on Income and Living Conditions (EU-SILC) and multi-level modeling techniques, this paper explores the macro-level determinants of the gender poverty gap in the ten post-socialist European Union member states. In dialogue with the literature on the impact of economic development on gender inequality in Asia and Latin America, we find that fast-paced, foreign capital led economic growth is associated with a larger gender poverty gap in Central and Eastern Europe, while generous welfare policies, specifically higher levels of spending on pensions and family policies are correlated with women's lower relative destitution. These findings evaluate the impact of neo-liberal style "economic development" on gender inequality in a geo-politically specific context and suggest that structural adjustment and global market integration may exacerbate women's vulnerability even when they are well equipped with human capital and other resources to compete with men in the labor market.
Keywords: J16; P36; I32; C21; 330; economic development; poverty; gender; SILC